Core-Binding Factor Influences the Disease Specificity of Moloney Murine Leukemia Virus - Lewis, Amy F. (American Society for Microbiology, 1999)
The core site in the Moloney murine leukemia virus (Moloney MLV) enhancer was previously shown to be an important determinant of the T-cell disease specificity of the virus. Mutation of the core site resulted in a significant shift in disease specificity of the Moloney virus from T-cell leukemia to erythroleukemia. We and others have since determined that a protein that binds the core site, one of the core-binding factors (CBF) is highly expressed in thymus and is essential for hematopoiesis. Here we test the hypothesis that CBF plays a critical role in mediating pathogenesis of Moloney MLV in vivo. We measured the affinity of CBF for most core sites found in MLV enhancers, introduced sites with different affinities for CBF into the Moloney MLV genome, and determined the effects of these sites on viral pathogenesis. We found a correlation between CBF affinity and the latent period of disease onset, in that Moloney MLVs with high-affinity CBF binding sites induced leukemia following a shorter latent period than viruses with lower-affinity sites. The T-cell disease specificity of Moloney MLV also appeared to correlate with the affinity of CBF for its binding site. The data support a role for CBF in determining the pathogenic properties of Moloney MLV.